Estrogen replacement therapy reverses spatial memory loss and pyramidal cell neurodegeneration in the prefrontal cortex of lead-exposed ovariectomized Wistar rats - Abiodun Shukrat Lasisi-Sholola; Sodiq Opeyemi Hammed; Richard Adedamola Ajike; Roland Eghoghosoa Akhigbe; Oladele Ayobami Afolabi (Current Research in Toxicology)
Background: Although menopause is a component of chronological aging, it may be induced by exposure to heavy metals like lead. Interestingly, lead exposure, just like the postmenopausal state, has been associated with spatial memory loss and neurodegeneration; however, the impact of hormone replacement therapy (HRT) on menopause and lead-induced spatial memory loss and neurodegeneration is yet to be reported. Aim: The present study investigated the effect and associated mechanism of HRT on ovariectomized-driven menopausal state and lead exposure-induced spatial memory loss and neurodegeneration. Materials and methods: Thirty adult female Wistar rats were randomized into 6 groups (n = 5 rats/group); the sham-operated vehicle-treated, ovariectomized (OVX), OVX + HRT, lead-exposed, OVX + lead, and OVX + Lead + HRT groups. Treatment was daily via gavage and lasted for 28 days. Results: Ovariectomy and lead exposure impaired spatial memory deficit evidenced by a significant reduction in novel arm entry, time spent in the novel arm, alternation, time exploring novel and familiar objects, and discrimination index. These findings were accompanied by a marked distortion in the histology of the prefrontal cortex, and a decline in serum dopamine level and pyramidal neurons. In addition, ovariectomy and lead exposure induced metabolic disruption (as depicted by a marked rise in lactate level and lactate dehydrogenase and creatinine kinase activities), oxidative stress (evidenced by a significant increase in MDA level, and decrease in GSH level, and SOD and catalase activities), inflammation (as shown by significant upregulation of myeloperoxidase activity, and TNF-α and IL-1β), and apoptosis (evidenced by a rise in caspase 3 activity) of the prefrontal cortex. The observed biochemical and histological perturbations were attenuated by HRT. Conclusions: This study revealed that HRT attenuated ovariectomy and lead-exposure-induced spatial memory deficit and pyramidal neurodegeneration by suppressing oxidative stress, inflammation, and apoptosis of the prefrontal cortex.